Teamwork in business students: Attitude is the key - Araya-Pizarro, Sebastián (2024)
Introduction: Currently, teamwork is considered a key factor for achieving organizational results, and therefore it is recognized as a fundamental skill in the education of university students of the business field. Objective: To analyze the propensity and attitude towards teamwork in business students from a Chilean university. Method: The study with a quantitative approach, non-experimental design and descriptive-transversal type, used the survey (n=215) as a data collection technique, whose questionnaire was based on the work of Mendo-Lázaro et al. (2017) for the measurement of attitudes towards teamwork (CACTE). The collected data were examined using a descriptive, inferential and multivariate statistical analysis (binary logistic regression). Results: It was found that the students prefer to work collectively; and that academic and socio-affective attitudes have a significant impact on their predilection. Therefore, it is concluded that in order to improve the intention to work in a team, it is essential to attend to the student’s attitudinal component.